Pengaruh Citra Merek Dan Persepsi Kualitas Produk Terhadap Keputusan Pembelian Hand Sanitizer Dettol Pada Masa Pandemi Covid-19 (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2017-2019) - Yuni Wulandari; Nurhajati Nurhajati; Muhammad Ridwan Basalama (UNIVERSITAS ISLAM MALANG, 2021)
Abstract The purpose of this study was to examine and analyze the effect of brand image and perceived product quality simultaneously on purchasing decisions for Dettol hand sanitizers during the Covid-19 pandemic, the effect of brand image on purchasing decisions for Dettol hand sanitizers during the Covid-19 pandemic, and the influence of perception. product quality towards the decision to purchase Dettol hand sanitizers during the Covid-19 pandemic. In this study, the total population of students from the Faculty of Economics and Business, Islamic University of Malang, class 2017-2019 who have purchased Dettol hand sanitizer is unknown, therefore this sampling uses the Malhotra theory of 90 respondents. Based on the data collection, the researcher analyzed the data through multiple linear regression tests. This data analysis produces the following information: 1) Brand image and perceived product quality can simultaneously have a positive and significant effect on the decision to purchase Dettol hand sanitizers during the Covid-19 pandemic for students of the Faculty of Economics and Business, Islamic University of Malang, class 2017-2019, 2 ) Brand image has a positive and significant effect on the decision to purchase Dettol hand sanitizer during the Covid-19 pandemic for students of the Faculty of Economics and Business, Islamic University of Malang, class 2017-2019, 3) Perception of product quality has a positive and significant effect on the decision to purchase Dettol hand sanitizer at the time Covid-19 pandemic in students of the Faculty of Economics and Business, Islamic University of Malang, class of 2017-2019.Keywords: Brand Image, Perceptions of Product Quality, Purchase Intention During Pandemic.